Asian American Spring Festival 1987 Flyer 06 (SJSU Asian American Studies Department, 2024)
Flyer for the Asian American Spring Festival Cultural Day, held on Wednesday, April 1 at 11:00 AM – 2:00 PM in the Amphitheater. Event included Japanese jazz and folk dancing by Judy Sakai, Kendo (Japanese martial arts), Japanese folk dancing, and Filipino folk dancing.